Evaluation of Arabic Large Language Models on Moroccan Dialect - Qarah, Faisal; Alsanoosy, Tawfeeq (Engineering, Technology & Applied Science Research, 2025)
Large Language Models (LLMs) have shown outstanding performance in many Natural Language Processing (NLP) tasks for high-resource languages, especially English, primarily because most of them were trained on widely available text resources. As a result, many low-resource languages, such as Arabic and African languages and their dialects, are not well studied, raising concerns about whether LLMs can perform fairly across them. Therefore, evaluating the performance of LLMs for low-resource languages and diverse dialects is crucial. This study investigated the performance of LLMs in Moroccan Arabic, a low-resource dialect spoken by approximately 30 million people. The performance of 14 Arabic pre-trained models was evaluated on the Moroccan dialect, employing 11 datasets across various NLP tasks such as text classification, sentiment analysis, and offensive language detection. The evaluation results showed that MARBERTv2 achieved the highest overall average F1-score of 83.47, while the second-best model, DarijaBERT-mix, had an average F1-score of 83.38. These findings provide valuable insights into the effectiveness of current LLMs for low-resource languages, particularly the Moroccan dialect.